Identification of vulnerable lines in power grids with wind power integration based on a weighted entropy analysis method. (3rd August 2017) - Fang, Ruiming; Shang, Rongyan; Wang, Yandong; Guo, Xinhua
Abstract: Vulnerable overhead electricity lines are a cause of serious risk to power distribution grids as damage can be the cause of large scale blackouts and cascading failures. With the integration of large scale wind power into generating capacity, both the topology structure and the distribution characteristics of power flow in distribution grid have undergone various changes that have increased line vulnerability. A novel approach to identify vulnerable lines based on the weighted entropy analysis method is proposed in this paper. In this approach, an assessment index, named the incremental power flow entropy, is first developed, which is used to describe influences caused by variation of the lines' capability of carrying power flow transfers on the vulnerability of the lines themselves at the same aggregation level. A second assessment index, named structural importance, describes the structural changes of a power grid that are caused by the integration of wind-generated electric power. The two assessment indices then are merged into one index by using the entropy weight analysis method, which can assess the vulnerability of the lines from the two aspects of power flow transmission and structural links. Vulnerability analysis under different situations, such as with and without the integration of the wind farm, and sharp fluctuations in wind speed at the wind farm, were carried out on an IEEE 39-bus system integrated with a 75 MW wind farm. Simulation results verified that the proposed assessment index not only can identify the vulnerable lines in a power grid with wind farm integration but also accurately reflected the vulnerability of the internal lines of the wind farm itself. Highlights: The influences of the transmission lines' capability of carrying load flow transfers on the vulnerability of the lines. The impact of wind powers on the topology structure and the load flow of power grid. The identification of vulnerable lines in power grid with wind farm integration.